Magnetism and magnetoelectricity in the polar oxide α-Cu2V2O7 - Lee, Y.-W.; Jang, T.-H.; Dissanayake, S. E.; Lee, Seunghun; Jeong, Yoon H. (Europhysics letters, 2016)
Single crystals of the orthorhombic polar oxide α-Cu2V2O7 with space group Fdd2 are synthesized and their physical properties are measured. Neutron powder diffraction is also performed on a polycrystal sample to extract the magnetic structure. The ground state is shown to be weakly ferromagnetic, that is, collinearly antiferromagnetic in the a-direction with a small remanent magnetization in the c-direction. When an external magnetic field is applied in the c-direction, further spin canting, accompanied by the induced electric polarization, occurs. It is demonstrated that the magnetoelectric effect in α-Cu2V2O7 is adequately described if spin-dependent hybridization due to spin-orbit coupling as well as magnetic domain effects are simultaneously taken into account. We discuss the implication of the present result in the search for materials with multiferroicity and/or magnetoelectricity.